Causal Relationships Between Exchange Rates And Stock Prices In Malaysia And Thailand During The 1997 Currency Crisis Turmoil - Venus, Khim-Sen Liew; Huzaimi, Hussain (University Library of Munich, Germany., 2004)
Using Granger (1969), Sim (1972) and Geweke et al. (1982) causality tests, this study finds a feedback causal relationship between exchange rate and stock price in Malaysia, whereas a unidirectional causal relationship running from exchange rate to stock price in Thailand. The stock markets of these countries are also found to be closely linked, with a feedback causal relationship between them. Most importantly, this study is able to identify the path through which the fall in Thai baht was transmitted to Malaysian ringgit plunge during the 1997 Currency Crisis turmoil.